Comparing the environmental impact of different hydrometallurgical processes for the recycling of lithium-ion batteries using a life cycle assessment approach - Maritz, Roelof Frederick (Stellenbosch : Stellenbosch University, 2024)
Thesis (PhD)--Stellenbosch University, 2024.